Economic progress of agriculture in Developing Nations 1950-68 - United States. Department of Agriculture,Economic Research Service, Foreign Development and Trade Division (Washington D.C. : Dept. of Agriculture Economic Research Service Foreign Development and Trade Division, 1970)
Developing countries will need to achieve larger gains in agricultural productivity this decade than in the fifties or sixties if real incomes of farm people are to rise and agriculture is to make a significant contribution to national income growth. These countries, as a group, increased agricultural output 2.8 per cent. a year during the past two decades, about as rapidly as the industrial countries tout only a little more than annual (population growth of 2.5 per cent. Output per farm worker grew less than 1 per cent. a year and output per hectare only 1.5 per cent. Among the 54 countries studied, 17 coun- tries increased agricultural output 4 per cent. or more a year, but output did not keep pace with population growth in 13 countries. Detailed studies of seven countries-Greece, Taiwan, Mexico, Colombia, Brazil, India, and Nigeria-show that many factors influence agricultural development. Developing countries will need expanding markets for farm products, large purchases of fertilizer and other non-farm resources, development of land and water resources, and improvements in farm technology to accelerate economic progress in agriculture.
lje 05/07/2017
Loans
Keywords: Agriculture---Economic aspects; Agricultural industries; Agricultural production; Agriculture; Developing Countries